2017
DOI: 10.19082/4300
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among mammographic findings with histopathologic type of breast cancer and human epidermal growth factor receptor 2 (HER2) in young women

Abstract: IntroductionRadiological measures to diagnose breast cancer, including mammographic and ultrasound assessments in young women, are associated with restrictions affecting the use of this tool. No adequate information is available on mammography view in young people with breast cancer and its relationship with pathologic type and epidermal growth factor receptor 2 (HER2) as a prognostic marker, especially in the Iranian race. This study was conducted to examine the relationship between mammographic findings of y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Margins of mass did not vary significantly with HER2/neu scores on DM or DBT. Farrokh et al [14] also showed no significant correlation between margins of masses and HER2/neu status. However, on DBT, spiculated margins were more frequently seen with increasing intensity of HER2/neu positivity in our study, demonstrating its superiority over DM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Margins of mass did not vary significantly with HER2/neu scores on DM or DBT. Farrokh et al [14] also showed no significant correlation between margins of masses and HER2/neu status. However, on DBT, spiculated margins were more frequently seen with increasing intensity of HER2/neu positivity in our study, demonstrating its superiority over DM.…”
Section: Discussionmentioning
confidence: 99%
“…[15] In a systematic review and meta-analysis by Elias et al in 2014, it was found that the presence of microcalcifications increased the chance of HER2/neu overexpression, which was not dependant on the presence or absence of associated mass. [514] Some studies showed a correlation specific to fine linear/branching microcalcifications. [5]…”
Section: Discussionmentioning
confidence: 99%
“…Clinical factors such as age, sex, smoking, and drinking cannot effectively predict tumour mutation status. Meanwhile, multiple studies have demonstrated that classic imaging characteristics, including breast density [ 30 ], a spiculated mass [ 31 ], and microcalcifications [ 32 ] on mammograms, are strongly correlated with HER2 status. However, the predictive capability of these characteristics for HER2 status is limited.…”
Section: Discussionmentioning
confidence: 99%
“…The malignant HA microcalcifications can present in a variety of different shapes (e.g., needle like or pleomorphic) and sizes (ranging from 40 to several hundred microns). There is increasing evidence that the presence of HA microcalcifications correlates with more aggressive disease, correlating with lymph invasion and Her-2 expression [ 7 , 8 ]. Castronovo and Bellahcene [ 9 ] have suggested that the deposition of HA in breast cancer is an active process rather than mineralization of cellular debris or necrotic material.…”
Section: Introductionmentioning
confidence: 99%